2019
DOI: 10.3390/mi10010075
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Drain Engineered InGaN Heterostructure Tunnel Field Effect Transistor

Abstract: A drain engineered InGaN heterostructure tunnel field effect transistor (TFET) is proposed and investigated by Silvaco Atlas simulation. This structure uses an additional metal on the drain region to modulate the energy band near the drain/channel interface in the drain regions, and increase the tunneling barrier for the flow of holes from the conduction band of the drain to the valence band of the channel region under negative gate bias for n-TFET, which induces the ambipolar current being reduced from 1.93 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that exploiting the polarization properties of III-nitride alloy heterostructures in TFETs design, such as InN/GaN and InGaN/AlInN, can notably increase the carrier tunneling probability, thereby enhancing both the ON-state current ( I ON ) and I ON / I OFF . This strategy has gained great attention in TFET applications. In III-nitride heterostructures, the mismatch in lattice constants of different materials can induce strain in the crystal, generating piezoelectric polarization effects at the heterojunction interface. The difference of spontaneous polarizations together with the piezoelectric polarization in the heterostructure will produce polarization surface charges at the interface of heterojunction, thereby augmenting the interface electric field and increasing tunneling probability. Although there exists strong polarization electric field in the InN/GaN heterojunction TFETs, the deep quantum well (QW) generated at the heterointerface will deteriorate the switching characteristics of the device simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that exploiting the polarization properties of III-nitride alloy heterostructures in TFETs design, such as InN/GaN and InGaN/AlInN, can notably increase the carrier tunneling probability, thereby enhancing both the ON-state current ( I ON ) and I ON / I OFF . This strategy has gained great attention in TFET applications. In III-nitride heterostructures, the mismatch in lattice constants of different materials can induce strain in the crystal, generating piezoelectric polarization effects at the heterojunction interface. The difference of spontaneous polarizations together with the piezoelectric polarization in the heterostructure will produce polarization surface charges at the interface of heterojunction, thereby augmenting the interface electric field and increasing tunneling probability. Although there exists strong polarization electric field in the InN/GaN heterojunction TFETs, the deep quantum well (QW) generated at the heterointerface will deteriorate the switching characteristics of the device simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The design is intended to operate as fast as the human brain with low power consumption and high integration density. Duan et al [7] propose a drain engineered InGaN heterostructure field effect transistor (DE-HTFET) which uses an additional metal on the drain region to modulate the energy band near the drain/channel interface. Their design showed a reduction in the subthreshold swing by 53.3% and a doubling of ION compared to nonpolar DE-HTFETs.…”
mentioning
confidence: 99%